Mapping the research framework and key trends of coral reefs in the South China Sea - Junhui Chen; Junhui Chen; Junhui Chen; Junhui Chen; Fei Tang; Fei Tang; Fei Tang; Heshan Lin; Heshan Lin; Heshan Lin; Bo Huang; Bo Huang; et al. (Frontiers in Marine Science, 2025)
The South China Sea, a key biodiversity hotspot in the Central Indo-Pacific, hosts a rich array of coral reef species and marine life but faces growing threats from climate change and human activities. This study systematically analyzes coral reef research in the region using a bibliometric analysis of records from the Web of Science Core Collection. The analysis highlights the diverse roles of contributing countries and their collaborations, with China emerging as a significant contributor to the regional scientific output. Our findings categorize the research into five principal themes through text mining and bibliographic coupling: (1) fundamental physical-biological interactions within reef systems, (2) biodiversity and symbiotic relationships in response to environmental stress, (3) climatic influences and the adaptive responses of reef systems, (4) conservation strategies and management practices for reef resilience, and (5) remote sensing and algorithmic approaches for reef mapping and monitoring. The discussion addresses regional challenges, outlines the identified research framework, and details key trends in South China Sea coral reef research, thereby providing essential information to guide future development and conservation efforts.